Rajya sabha at work - Devi, V. S. Rama (New Delhi, 2017)
A bold and pioneering initiative was taken in 1996 to bring out the first edition of the publication titled ?Rajya Sabha at Work?. It elaborately and comprehensively documented the procedures and practices relating to the functioning of the Rajya Sabha since its first sitting on 13 May 1952 and encapsulated in its scope the evolution of Rajya Sabha and its functioning over the years, the changes made in its rules of procedures and practices and other developments concerning the conduct of its proceedings. We are indebted to late Smt. V.S. Rama Devi, former Director, Rajya Sabha Secretariat for painstakingly compiling and bringing out this noteworthy publication. A number of developments including substantive change in practices and procedures of the House, new ruling from the Chair, etc have taken place since the second edition was brought out a decade ago and therefore, a need was felt to have an updated and revised edition of the book. This revised edition is intended to fulfil this need.
Keywords: Legislative Process